FEATURES OF CHANGES IN THE RECLAMATIVE STATE AND SOIL FERTILITY BY REGULAR IRRIGATION AND IN THE POST-RECLAMATION PERIOD OF THE SOUTHERN RUSSIAN LANDS - Babichev Alexandr N.; Dokuchayeva Lidiya M.; Yurkova Rita Ye. (Мелиорация и гидротехника, 2023)
Purpose: to reveal the features of changes in the reclamative state and soil fertility of the lands in the southern Russia by regular irrigation and in the post-reclamation period. Discussion. The reasons for raising the water table (GWL) by regular irrigation are considered: the location of systems in the floodplains of rivers or on terraces I and II, the design of large irrigation plots with an area of about 1000 hectares on irrigation systems, the design and construction of canals and an irrigation network in an earthen channel etc. The main factors influencing the deterioration of the reclamative state and the soil fertility decrease of irrigated land (secondary salinization, alkalinization, waterlogging, overconsolidation, dehumification, etc.) are natural and technogenic factors. Natural ones are climate, geological structure, geomorphological conditions, relief, natural drainage of lands, geochemical and hydrogeological conditions, types and properties of soils (filtration, etc.), their natural salinity and alkalinity, fertility, etc. Technogenic ones are the efficiency of irrigation systems and their water supply, irrigation methods and technique, irrigation regime, irrigation map planning, types and parameters of drainage systems, quality of surface and drainage waters used for irrigation, technical level of operation of irrigation and drainage systems. Conclusions. The decrease in water load in the post-reclamation period, in the presence of natural and artificial drainage contributed to a decrease of water table and partially secondary salinization, alkalinization, while the soils do not reach the background levels in general. During the reconstruction and construction of new irrigation systems, the complexity and sequence of the measures taken to prevent the increase in GWL, salinization and alkalinization of soils should be observed.